SHORT STORY TEXT TEACHING MATERIALS ORIENTED ON CRITICAL THINKING ABILITY FOR HIGH SCHOOL STUDENTS - Nurul Inayah; Abdul Rozak; Dede Endang Mascita (Bajang Institute, 2023)
This research was to obtain digital teaching materials for short story texts oriented towards critical thinking skills for high school students. Learning is an activity planned and facilitated by the teacher which aims to change student behavior for the better. Teaching materials can help and guide students in carrying out learning activities so that students' mastery of the subject matter becomes better. Short stories are stories that are physically short and can be read in one sitting. The research method that the author will use in this study is the Research and Development (R&D) method. This study uses the ADDIE research and development model method. The ADDIE development design stages are as follows: analysis, design, development, implementation, and evaluation. Aspects of content or material obtained a percentage of 81,25%, aspects of presentation of material obtained a percentage of 75,00%, aspects of language and readability obtained a percentage of 81,25%, graphic aspects obtained a percentage of 90,00%. The results of the overall percentage of four aspects, namely content or material aspects, material presentation aspects, language and readability aspects, and graphic aspects obtained a score of 82.45%. Based on the results of these scores, the digital learning module for short story texts oriented towards critical thinking skills is included in the sufficiently valid criteria. Based on the results of the analysis of students' needs for teaching materials by the teacher and students, it can be concluded that students need teaching materials for short story texts oriented towards thinking skills for class XI high school students. Short story text learning modules oriented towards critical thinking skills for class XI high school students can be used as an alternative learning, because this teaching material is in accordance with the demands of the curriculum and according to the needs of students